The development of Chinese grammar checker website based on Natural Language Processing. Issue 4 (March 2020) - Wangi, J; Rosalin, K; Theresia,
Abstract: Research on artificial intelligence in learning Mandarin in Indonesia is still very rare. The research on developing a Chinese grammar checking website is aimed at helping Mandarin learners in mastering Mandarin grammar. This website can be a "learning companion" of basic-level Mandarin learners outside the classroom. This technology is still very new, so this research should be carried out immediately by researchers in Indonesia to master this technology. The method used in this research is a quantitative approach. The collection of grammar patterns that will appear on the chineseteak.net will be selected from several Chinese textbooks. Then the pattern will become Mandarin grammar patterns and will be entered the website auto-correct grammar. This website is designed using PHP and MySQL as the database. From the results of the questionnaire, we can find out that there are 7 points of Mandarin grammar that are still difficult for early learners.